An Efficient Finite-Difference Time-Domain Algorithm to Simulate the Absorbed Energy of Nonflat Layers or Particles of Thin-Film Solar Cells - Byun, Seok Yong; Byun, Seok-Joo; Sheen, Dongwoo; Lee, Taek-Sung (IEEE-INST ELECTRICAL ELECTRONICS ENGINEERS INC, 2015)
We propose an efficient and accurate finite-difference time-domain (FDTD) algorithm to simulate the absorbance of a thin-film solar cell containing nanometer particles or nonflat layers. This algorithm can extract a closed boundary for an arbitrarily shaped object, with the solar cell model being discretized into a set of Yee's cells to construct the FDTD system. Using this information, we can distinguish the closed boundaries of the components (e.g., particles or layers) of the solar cell and accurately calculate the absorbance of each particle or layer. Moreover, using the closed line (in 3-D, surface) integration instead of the area (in 3-D, volume) integration enables faster calculation and requires less memory.
Keywords: SILICON NANOWIRE ARRAYS; OPTICAL-ABSORPTION; LIGHT-ABSORPTION; BACK-CONTACT